الحركة الوطنية بمنطقة مسعد وتأثير بعض الشخصيات الشيوعية فيها (1927م-1951م) - زيان إسماعيل (University of Eloued جامعة الوادي, 2024)
تعدّ دراسة تاريخ الحركة الوطنية في الجزائر من أهمّ الدراسات التي أُعْطِيَ لها مجال كبير من البحث والتحليل في ظلّ توفّر المادة التاريخية لذلك، لكنّها اقتصرت في معظمها على المناطق الشمالية من الوطن كالعاصمة وقسنطينة ووهران، أمّا الجنوب الجزائري بمُدُنِهِ وقراه لم تتوسع الأبحاث بشمله بالدراسة، مع أنّ قيادات الحركة تنقّلوا مرارا وتكرارا لتلك المناطق، بل وصنعوا فيها مناضلين أصبحوا فيما بعد رموزا للوطنية والاستقلال. ومن منطلق ما سبق تأتي هذه الورقة لدراسة تأثير بعض الشخصيات الشيوعية في الحركة الوطنية لمنطقة مسعد التابعة للجلفة، وذلك من خلال استنطاق الأرشيف الفرنسي من صحف وجرائد وتقارير عسكرية، وأخُصُّ بالبحث المناضل الجزائري محمود بن لكحل والمعلم والكاتب الفرنسي جون-جاك غالو . The study of the national movement history in Algeria is considered one of the most important studies to which a large scope of research and analysis was given in light of the historical material availability for it, but it was mostly limited to the northern regions of the country such as of Algeria, Constantine and Oran. As for the south of Algeria, with its cities and villages, the research didn’t expand to include it in the study, although the movement’s leaders visited repeatedly to those areas and even created activists there who later became patriotism symbols and independence. Based on the above, this paper comes to study some communist figurers influence in the national movement in Messaad region, by interrogating the French archives of newspapers, journals, and military reports, and in particular the research includes the Algerian activist Mahmoud Ben Lakhal and the French teacher and writer JeanJacques Galland.
"محمود بن لكحل" و"جون-جاك غالو" أنموذجا
Keywords: الحركة الوطنية; مسعد; محمود بن لكحل; جون جاك غالو; انتخابات; National Movement; Messaad; Mahmoud Ben Lakhal; Jean-Jacques Galland; Elections